Impact of overland flow on soil characteristics in Třebsín experimental plots - Hana BAČINOVÁ; Pavel KOVÁŘ (Soil and Water Research, 2017)
This paper describes the continuation of simulated outcomes from the plots No. 4 and No. 5 with two different soils, using the KINFIL model to assess the runoff from extreme rainfall. The KINFIL model is a physically-based, parameter-distributed 3D model that has been applied to the Třebsín experimental station in the Czech Republic. This model was used for the first time in 2012 to simulate the impact of overland flow caused by natural or sprinkler-made intensive rains on four of the nine experimental plots. This measurement of a rain simulator producing a high-intensity rainfall involves also hydraulic conductivity, soil sorptivity, plot geometry and granulometric curves to be used for the present analysis. However, since 2012, the KINFIL model has been amended to provide a more effective comparison of the measured and computed results using the values of new parameters such as storage suction factor and field capacity on plot 4 and plot 5. The KINFIL model uses all input data mentioned above, and it produces the output data such as gross rainfall, effective rainfall, runoff discharge hydraulic depths, hydraulic velocities and shear velocities as well as shear stress values depending on the soil particle distribution. These processes are innovative, physically based, and both the measured and the computed results fit reliably.